Edisi 1 Vol 2 September 2023 MEMBANGUN UMAT DENGAN ZAKAT: POTENSI ZAKAT DI INDONESIA DAN STRATEGI REALISASINYA - Solekhan, Ahmad (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2023)
The potential for incoming ZISWAF funds(Zakat, infaq, Shodaqoh and Waqf) among Muslims in Indonesia is very large. TheBAZNAS Strategic Study Center for 2021which shows the estimated figure for obtaining ZIS funds that are traditionally managed in the community (non-OPZ) in 2019-2020 reaches IDR 61.26 trillion. Even if the formal and informal ZIS realization figures are added up, the space for ZIS collection is still very wide when compared to its potential. Therefore, there is a need for ZIS collection innovation so that it can grow significantly. One form of effort that can be done to give muzaki trust and satisfaction in managing zakat is to provide good and structured services that refer to the five functions of organizational management namely planning (planning), grouping (organizing), implementation (activating) evaluation (evaluating) and supervision(controlling) as a form of efforts to promote business development.